Gods of jade and shadow eaudiobook - Moreno-Garcia, Silvia (Random House Audio, 2019)
The Mayan god of death sends a young woman on a harrowing, life-changing journey in this dark, one-of-a-kind fairy tale inspired by Mexican folklore. “ A spellbinding fairy tale rooted in Mexican mythology . . .  Gods of Jade and Shadow  is a magical fairy tale about identity, freedom, and love, and it's like nothing you've read before.”— Bustle NEBULA AWARD FINALIST • NAMED ONE OF THE BEST BOOKS OF THE YEAR BY NPR •  Tordotcom  • The New York Public Library •  BookRiot The Jazz Age is in full swing, but Casiopea Tun is too busy cleaning the floors of her wealthy grandfather’s house to listen to any fast tunes. Nevertheless, she dreams of a life far from her dusty small town in southern Mexico. A life she can call her own.  Yet this new life seems as distant as the stars, until the day she finds a curious wooden box in her grandfather’s room. She opens it—and accidentally frees the spirit of the Mayan god of death, who requests her help in recovering his throne from his treacherous brother. Failure will mean Casiopea’s demise, but success could make her dreams come true. In the company of the strangely alluring god and armed with her wits, Casiopea begins an adventure that will take her on a cross-country odyssey from the jungles of Yucatán to the bright lights of Mexico City—and deep into the darkness of the Mayan underworld. Praise for Gods of Jade and Shadow “A dark, dazzling fairy tale . . . a whirlwind tour of a 1920s Mexico vivid with jazz, the memories of revolution, and gods, demons, and magic.” —NPR “Snappy dialog, stellar worldbuilding, lyrical prose, and a slow-burn romance make this a standout. . . . Purchase where Naomi Novik, Nnedi Okorafor, and N. K. Jemisin are popular.” — Library Journal  (starred review) “A magical novel of duality, tradition, and change . . . Moreno-Garcia’s seamless blend of mythology and history provides a ripe setting for Casiopea’s stellar journey of self-discovery, which culminates in a dramatic denouement. Readers will gladly immerse themselves in Moreno-Garcia’s rich and complex tale of desperate hopes and complicated relationships.” — Publishers Weekly  (starred review)